Car independence in an automobile society? The everyday mobility practices of residents in a car-reduced housing development - Selzer, Sina; Lanzendorf, Martin (Travel, behaviour & society, 2022)
•Applies a biographically inspired practice-theoretical approach to understand everyday mobility from car-reduced neighborhoods.•Investigates various ‘contexts’ and ‘practice bundles’ that shape car-(in)dependent mobility practices.•Material, personal-temporal, and socio-cultural contexts of residents’ travel behavior in car-reduced neighborhoods stabilize and support car-independent mobility.•The meanings (including emotions and feelings) of mobility practices determine their performance type.•Calls for more car-reduced planning for the transition to low-carbon mobility. Lately, transport researchers and practitioners are showing renewed interest in car-reduced neighborhoods and their residents’ mobility to investigate possible factors influencing sustainable transport. With a biographically inspired practice-theoretical approach, this study considers the ‘context of travel behavior’ and, thus, focuses on mobility as a ‘practice’ in order to improve the understanding of everyday mobility as well as the potential and limitations of implementing car-reduced housing. Based on qualitative interviews with residents of two German car-reduced neighborhoods, we first identify different compositions of materials, competences, and meanings (including the feelings and emotions) of car-(in)dependent mobility practices. Second, we discover the personal, social, temporal, and socio-structural circumstances of the residents’ travel behavior alongside ‘practice bundles’ that interact with car-(in)dependent mobility. Finally, our findings indicate, on the one hand, that the car-centric material context outside car-reduced neighborhoods, the incorporation of private car driving with the practice of everyday life, and the affective satisfaction with car use and ownership negatively influence car independence. On the other hand, our results highlight that residential location and its materiality in the case of car-reduced housing developments, as well as the personal-temporal and socio-cultural contexts of their residents’ mobility practices stabilize and support car independence and low-carbon mobility.